Entrepreneurship, self-employment and job creation in Vietnam - Tran, Trang (SLU/Dept. of Economics, 2019)
Entrepreneurship has contributed to the social, economic development. A wave of entrepreneurship has been witnessed in emerging countries, including Vietnam. It is considered as one of the most important concerns of the Government to boost the economy. The aims of this thesis are to understand the motivations for Vietnamese to become entrepreneurs, the relationship between entrepreneurship with self-employment as a career choice, and the contribution to job creation. The study is based on the push and pull effects theory and entrepreneurship and its relationship with self-employment and job creation. The main method in the study is a qualitative approach through conducting four semi-structured interviews with Vietnamese entrepreneurs from different business areas. The key finding is that Vietnamese take into consideration both push and pull effects to become entrepreneurs. However, pull effects are more considerable than the push effects. Entrepreneurs own a high work effort, and independent attitudes, whereas the attitudes to risks are varied from different entrepreneurs. Furthermore, they are all aware of the role of entrepreneurial activities in job creation.